Clostridium perfringens in a total hip arthroplasty: An unusual cause of prosthetic joint infection, treated with one-stage revision: A case report - Dorien Peters; Linda Martine Kampschreur; Loredana Elena Pirii; Wierd Pieter Zijlstra (Journal of Orthopaedic Reports)
Background: Prosthetic Joint Infection (PJI) is a serious complication after total hip arthroplasty (THA). PJI is the most common reason for revision surgery on patients with arthroplasty, leading to prolonged hospitalization, repeated surgical intervention, and sometimes in definitive loss of the implant. Clostridium perfringens causing PJI is highly unusual. Case report: In this case, we describe the diagnostic and therapeutic challenges of a Clostridium perfringens Prosthetic Joint Infection following a total hip arthroplasty in an elderly woman. Conclusion: This case is unique because it is the first published PJI with C. perfringens, successfully treated by a one-stage infection revision combined with twelve weeks of antibiotics. Despite an extensive work up, a PJI or C. perfringens infection was not proven preoperatively. Perioperative tissue and sonication cultures were the cornerstone of the diagnosis. C. perfringens may be seen as an ‘easy to treat’ pathogen and successful treatment is possible with a one-stage infection revision and additional antibiotics for twelve weeks.